Two precatalysts for application in propargylic CH activation. Issue 10 (27th September 2019) - Möller, Saskia; Drexler, Hans-Joachim; Heller, Detlef
Abstract : The complexes [Rh(NBD)(DPEPhos)]BF4 and [Rh(COD)(DPEPhos)]BF4 ·CH2 Cl2 {DPEPhos is bis[(2‐diphenylphosphanyl)phenyl] ether, NBD is norborna‐2, 5‐diene and COD is cycloocta‐1, 5‐diene} are applied as precatalysts. In addition, the catalytically inactive pentacoordinated 18‐electron complex [RhCl(NBD)(DPEPhos)] was synthesized, which forms in the presence of chloride in the reaction system. Abstract : The complexes {bis[(2‐diphenylphosphanyl)phenyl] ether‐κ 2 P, P ′}(η 4 ‐norbornadiene)rhodium(I) tetrafluoridoborate, [Rh(C7 H8 )(C36 H28 OP2 )]BF4, and {bis[(2‐diphenylphosphanyl)phenyl] ether‐κ 2 P, P ′}[η 4 ‐( Z, Z )‐cycloocta‐1, 5‐diene]rhodium(I) tetrafluoridoborate dichloromethane monosolvate, [Rh(C8 H12 )(C36 H28 OP2 )]BF4 ·CH2 Cl2, are applied as precatalysts in redox‐neutral atomic‐economic propargylic CH activation [Lumbroso et al. (2013). Angew. Chem. Int. Ed. 52, 1890–1932]. In addition, the catalytically inactive pentacoordinated 18‐electron complex {bis[(2‐diphenylphosphanyl)phenyl] ether‐κ 2 P, P ′}chlorido(η 4 ‐norbornadiene)rhodium(I), [RhCl(C7 H8 )(C36 H28 OP2 )], was synthesized, which can form in the presence of chloride in the reaction system.